Literatur Riview Identifikasi Dan Klasifikasi Skincare Berdasarakan Permasalahan Kulit Wajah - Suhandi, Naila (Jurnal Tata Rias, 2024)
Facial skincare has become an integral part of the daily routine for many individuals, especially among women, to maintain the health and beauty of their skin. As time progresses, skincare products have become increasingly diverse, with various options claiming to address different skin concerns. However, many consumers face difficulty in choosing the right products, particularly because facial skin problems are highly varied. Therefore, this article aims to help the public better understand facial skin issues in more detail, enabling them to choose skincare products that are more suitable and aligned with their skin’s needs, which in turn will improve overall skin health. The research method used in this study is a literature review, analyzing various scientific articles related to the identification of skin types and the selection of skincare products. Consumers' decisions in choosing skincare products are greatly influenced by both internal and external factors. Internal factors, such as skin type and condition, play a key role in determining the right products, while external factors such as price, brand, packaging, and recommendations from others also play a significant role. Thus, despite the substantial benefits provided by technology, consumers still need to be wise in utilizing available information to avoid making incorrect decisions.